2019
DOI: 10.1002/celc.201900640
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electrochemical Hydrogenation of 5‐Hydroxymethylfurfural to 2,5‐Bis(hydroxymethyl)furan on Ag‐Displaced Nanotextured Cu Catalysts

Abstract: The hydrogenation of 5‐hydroxymethylfurfural (HMF), an important bio‐based platform chemical, to 2,5‐bis(hydroxymethyl)furan (BHMF), a promising building block for polymers, is conventionally conducted at high pressures of H2 in the presence of heterogeneous catalysts. Recently, electrochemical hydrogenation has emerged as a promising process for BHMF production; however, one challenge of this process is to improve the catalytic activity of the electrocatalyst. In this study, a series of AgCu electrocatalysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 39 publications
2
60
0
Order By: Relevance
“…Productivity decreases with the accumulated charge, starting from 0.708 mmol h À 1 cm À 2 after 20 C to 0.289 mmol h À 1 cm À 2 at the end of test, due to the decrease of HMF concentration with the reaction time in the batch cell. The same trend is reported in the literature for Ag/ Cu flat electrodes in the reduction of HMF 0.02 M at a similar potential, [7,9] but foam electrocatalysts in this work show a higher productivity for all the accumulated charges. For instance, Roylance et al reported a 0.127 mmol h À 1 cm À 2 productivity at 20 C (37 % HMF conversion and 99 % FE), [7] while the value obtained by Zhang et al is 0.052 mmol h À 1 cm À 2 (28 % HMF conversion and 100 % FE).…”
Section: Electrochemical Reduction Of Diluted Hmf Solutionssupporting
confidence: 90%
See 4 more Smart Citations
“…Productivity decreases with the accumulated charge, starting from 0.708 mmol h À 1 cm À 2 after 20 C to 0.289 mmol h À 1 cm À 2 at the end of test, due to the decrease of HMF concentration with the reaction time in the batch cell. The same trend is reported in the literature for Ag/ Cu flat electrodes in the reduction of HMF 0.02 M at a similar potential, [7,9] but foam electrocatalysts in this work show a higher productivity for all the accumulated charges. For instance, Roylance et al reported a 0.127 mmol h À 1 cm À 2 productivity at 20 C (37 % HMF conversion and 99 % FE), [7] while the value obtained by Zhang et al is 0.052 mmol h À 1 cm À 2 (28 % HMF conversion and 100 % FE).…”
Section: Electrochemical Reduction Of Diluted Hmf Solutionssupporting
confidence: 90%
“…GC‐MS analyses evidence the formation of 5‐methylfurfuryl alcohol and 5‐methylfurfural (Figure S10) and the presence of high molecular products. 5‐methylfurfuryl alcohol has been previously related to the presence of Cu; however, making a comparison between our work and the previous one is not straightforward because herein a larger volume of electrolytic solution is used and the size of the catalyst is different. The formation of dimers and oligomers as by‐products is reported by Roylance et al.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations